ANALISIS KEMAMPUAN VISUAL SPATIAL THINKING DALAM MENYELESAIKAN SOAL BERBASIS ETNOMATEMATIKA PADA PERMAINAN KELERENG - Jannah, Raudatul; Putra, Eric Dwi; Murtinasari, Frida (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
This research is a combination of visual and spatial thinking abilities which are very closely related. Visual-spatial thinking abilities involve the ability to understand and manipulate spatial relationships between objects, which includes the ability to visualize objects in space, understand orientation and position, and plan movement or changes in three-dimensional space. This research aims to analyze students' visual-spatial thinking abilities in solving ethnomathematics-based problems. The research subjects were taken from four class IX students, two students with high visual-spatial thinking abilities and two students with low visual-spatial thinking abilities. The research method in this study uses descriptive with a qualitative approach. The instruments used to collect data in this research were test and interview techniques. Furthermore, the data that has been obtained will be analyzed to determine the level of students' visual-spatial thinking abilities, the results of students' question answers will be strengthened by the results of interview answers conducted by researchers with selected subjects. Based on the results of this research, it was found that there were two students with high visual-spatial thinking abilities as indicated by the results of tests and interviews who had met the three indicators of visual ability, and students with low visual-spatial thinking abilities who had not been able to pass several of the ability visual indicators.